Child abuse, personality, and spirituality as predictors of happiness in maltese college students - Galea, Michael (Research in the social scientific study of religion, 2007)
This study examined the incremental validity of spirituality and religiosity controlling for personality and child abuse history among Maltese college students. A total of 214 female and 98 male undergraduates completed the Spiritual Transcendence Scale, the Brief Adjective Rating Scale, the Childhood Trauma Questionnaire, items about religious practices, a positive affect scale, a negative affect scale, and the Satisfaction with Life scale. Multiple regression analysis indicated that spirituality but not religious practices predicted positive affect and satisfaction with life after controlling for child abuse history and personality. The study suggests that spirituality may be an important potential source of resiliency for persons with a childhood history of abuse. Spirituality’s ability to predict positive but not negative affect suggests it may be especially suited as a useful variable in the positive psychology movement.